2017
DOI: 10.1128/iai.00546-17
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Pseudomonas aeruginosa by Chicken Cathelicidin-2 Is Immunogenically Silent, Preventing Lung Inflammation In Vivo

Abstract: The development of antibiotic resistance by Pseudomonas aeruginosa is a major concern in the treatment of bacterial pneumonia. In the search for novel anti-infective therapies, the chicken-derived peptide cathelicidin-2 (CATH-2) has emerged as a potential candidate, with strong broad-spectrum antimicrobial activity and the ability to limit inflammation by inhibiting Toll-like receptor 2 (TLR2) and TLR4 activation. However, as it is unknown how CATH-2 affects inflammation in vivo, we investigated how CATH-2-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…However, in instances where the bacteria are killed, both LL-37 and CATH-2 exhibit anti-inflammatory activity and can prevent activation via TLR2 and TLR4 183 . This is one of the mechanisms described for cathelicidin-mediated dampening of inflammatory responses induced by bacterial products, which may be especially important in pulmonary infections to protect the respiratory epithelium 173 .…”
Section: [H3] Crosstalk Of Chdp With Tlrsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in instances where the bacteria are killed, both LL-37 and CATH-2 exhibit anti-inflammatory activity and can prevent activation via TLR2 and TLR4 183 . This is one of the mechanisms described for cathelicidin-mediated dampening of inflammatory responses induced by bacterial products, which may be especially important in pulmonary infections to protect the respiratory epithelium 173 .…”
Section: [H3] Crosstalk Of Chdp With Tlrsmentioning
confidence: 99%
“…LL-37, CATH-2 and BMAP-28, hBD2, and synthetic peptides e.g. IDR-1 and IDR-1002, has been shown to control inflammation in various animal models of infections and sepsis 55, 57,59,60,[170][171][172][173] . Similarly, an LL-37-derived peptide controlled the disease process in a murine model of inflammatory arthritis 20 , and IDR-1002 effectively alleviated airway inflammation in vivo 21 .…”
Section: [H2] Regulation Of Inflammationmentioning
confidence: 99%
“…While LPS-cathelicidin interaction may be important for eliciting antimicrobial activity, it was first shown in 1994 by Hirata et al (64), that the 18 kDa rabbit cationic protein (CAP18) also exerts LPS-neutralizing activity, which drastically inhibits the inflammatory responses toward LPS both in vitro and in vivo (65)(66)(67). Later studies showed that this LPS-cathelicidin interaction resulted in reduced TLR4 activation and was not limited to hexa-acylated E. coli LPS (68)(69)(70)(71)(72), but was also observed in the context of penta-acylated P. aeruginosa LPS and the tetra-acylated P. gingivalis LPS (68,70,73). For several cathelicidins, including the human LL-37, it has now been shown that direct complex formation between LPS and cathelicidins plays an important role in preventing the binding of LPS to the TLR4 receptor complex, thereby reducing immune activation (66,(74)(75)(76)(77)(78)(79).…”
Section: Cathelicidins Inhibit Lps-induced Tlr4 Activationmentioning
confidence: 99%
“…Importantly, when instead bactericidal concentrations are used, inhibition of macrophage activation can be observed again. Alternatively, using cathelicidins that lack antimicrobial activity, but possess LPS-neutralizing activity, such as the canine K9CATH, it was shown that these peptides can in fact reduce macrophage activation in the context of killed bacteria, but not in the context of viable bacteria (73,77,92). This viability-dependent regulation of TLR activation provides an elegant way for the host to respond to bacterial molecules only when needed.…”
Section: Cathelicidin-mediated Tlr Regulation In Vitromentioning
confidence: 99%
“…CATHs exhibit antimicrobial activity against both grampositive and -negative bacteria, fungi, protozoa, and viruses [6,7]. CATHs also reportedly direct chemotaxis activity, induce chemokine release, modulate the differentiation of macrophages and dendritic cells, enhance phagocytosis, promote wound healing, and mobilize leukocytes via modulation of TLR activation [8].…”
Section: Introductionmentioning
confidence: 99%